Pc1-pulsations: the parallel structure in the magnetosphere plasma with the admixture of the heavy ions - Mikhailova, O.S.; Klimushkin, D.Yu.; Mager, P.N. (Advances in Astronomy and Space Physics, 2012)
The paper deals with the parallel structure of ultra-low frequency waves. To obtain the function describing the wave field we use the quasi-perpendicular approximation (k ̝ » k ֽֽ). Different regions of the wave propagation are studied.